CRISPR-Cas9 Genome Editing Technology for Zoonotic Disease Control in Indonesia: A Comprehensive Review - Adnyana, I Made Dwi Mertha; Eljatin, Dwinka Syafira; Sudaryati, Ni Luh Gede; Adiwinoto, Ronald Pratama; Raza, Syed Meesam; da Cruz , Zito Viegas (Journal of Medicine and Health Technology, 2024)
The increasing emergence of zoonotic diseases originating from vectors, rodents, mammals, and others has increased the potential for outbreaks of pandemics in the Indonesian territory. Although control and prevention have been implemented, these efforts have not yet revealed a bright spot; therefore, elaboration with advanced CRISPR-Cas9 technology is a way to accelerate efforts to control zoonotic diseases in Indonesia. However, there is limited literature on this topic. This review aims to comprehensively describe, identify, and summarize the application of CRISPR-Cas9 genome-editing technology in zoonotic disease control in Indonesia. Our findings show that CRISPR-Cas9 genome editing technology offers an innovative approach for zoonotic disease control by targeting disease vectors, modifying animal reservoirs, improving disease surveillance, enhancing vaccine development, and exploring traditional medicine candidates and immunotherapy. The high level of precision, efficiency, and versatility in targeting genomes capable of disrupting, damaging, and disrupting the disease transmission cycle in pathogens makes CRISPR-Cas9 highly effective. However, challenges such as off-target impacts, regulatory complexity, and ethical considerations must be overcome with inter- and multidisciplinary collaboration to promote transparency, equity, and public engagement throughout the process of implementing this technology in the field, especially in Indonesia.